The Independence of the South American Republics: a study in recognition and foreign policy (1916)
This publication presents international law that existed before the war of the American Revolution, is recognition. Shortly before 1776 a new state had come into existence, and the United Netherlands had won their independence from Spain in the sixteenth century, in order to be recognized by the powers of Europe in the sixteenth century, by the above, Switzerland is off domains of the Habsburgs and maintained its separate existence, Portugal also had established himself as an independent monarchy on the coast of Spain. / Abstract. Esta publicación expone el derecho internacional que no existía antes de la guerra de la Revolución Americana, es el del reconocimiento. Poco antes de 1776 un nuevo Estado había llegado a existir, así los Países Bajos Unidos habían ganado su independencia de España en el siglo XVI, para que se les reconociera por las potencias de Europa en el siglo XVI, por lo anterior, Suiza se desprendió de los dominios de los Habsburgo y mantuvo su existencia separada, también Portugal se había establecido como una monarquía independiente en la costa de España.